Stepwells of Rajasthan - Bahadur, V. N. (Gurgaon Shubhi Publications, 2016)
This book is a pictorial and anecdotal record of stepwells in Rajasthan.
Keywords: Stepwells-India-Rajasthan.; Stepwells-India-Rajasthan-Pictorial works